2020
DOI: 10.1371/journal.pone.0236896
|View full text |Cite
|
Sign up to set email alerts
|

The loss of nuclear expression of single-stranded DNA binding protein 2 of gastric adenocarcinoma and its prognostic role: Analysis of molecular subtype

Abstract: Single-stranded DNA binding protein 2 (SSBP2) is ubiquitously expressed, with several studies reporting it to be a tumor suppressor. We investigated SSBP2 expression and its clinicopathological significance in gastric cancer. SSBP2 expression was examined by immunohistochemistry in 539 gastric cancer sections. The cases were divided into three subtypes, namely, Epstein–Barr virus-associated (EBV), microsatellite unstable, and others (microsatellite stable and EBV negative), based on the molecular classificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Bang et al reported that loss of nuclear SSBP2 expression was correlated with higher pT stage, nodal metastasis, and higher AJCC stage in gastric adenocarcinoma. They also found that loss of nuclear SSBP2 expression was associated with poorer RFS in a microsatellite stable and Epstein–Barr virus (EBV)-negative group and HER2-negative group [ 14 ]. Chung et al reported that loss of nuclear SSBP2 expression was observed in 34.3% of colorectal adenocarcinoma (CRA) and 76.3% of metastatic CRA cases, and they noted that loss of nuclear SSBP2 expression was associated with higher pT stage, vascular invasion, and poorer OS in CRA [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Bang et al reported that loss of nuclear SSBP2 expression was correlated with higher pT stage, nodal metastasis, and higher AJCC stage in gastric adenocarcinoma. They also found that loss of nuclear SSBP2 expression was associated with poorer RFS in a microsatellite stable and Epstein–Barr virus (EBV)-negative group and HER2-negative group [ 14 ]. Chung et al reported that loss of nuclear SSBP2 expression was observed in 34.3% of colorectal adenocarcinoma (CRA) and 76.3% of metastatic CRA cases, and they noted that loss of nuclear SSBP2 expression was associated with higher pT stage, vascular invasion, and poorer OS in CRA [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…who were blinded to the clinicopathological parameters and the patient clinical outcomes. According to previous reports [ 14 , 16 ], we subdivided the patients into a positive subgroup (proportion of positive tumor cells >10% of the total tumor cells) and a negative subgroup (proportion of positive tumor cells <10% of the total tumor cells).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…SSBP2-null mice showed an enhanced predisposition to malignancy [7], and SSBP2 was downregulated in prostate cancer and esophageal squamous cell carcinoma cell lines and inhibited tumor cell growth [8,9]. Low SSBP2 expression at the protein level has been linked to an aggressive phenotype and unfavorable prognosis in some types of solid tumors [10][11][12][13]. However, studies on glioblastoma with an SSBP2-inherited variant [14] and hepatocellular carcinoma [15] showed that high SSBP2 expression was associated with poor clinical outcomes, suggesting an oncogenic role of SSBP2.…”
Section: Introductionmentioning
confidence: 99%